2012
DOI: 10.11599/germs.2012.1004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial activity of miswak, propolis, sodium hypochlorite and saline as root canal irrigants by microbial culturing and quantification in chronically exposed primary teeth

Abstract: Introduction One of the essential factors for successful root canal therapy is elimination of bacterial contaminants using an effective root canal chemical irrigant such as sodium hypochlorite which inherently possesses certain disadvantages like irritation to periapical tissues, staining of the instruments, burning of surrounding tissues etc. The aim of the study was to explore newer irrigant agents which would probably be as effective or more and at the same time less irritating to the tissues than sodium hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…This effect of propolis is possibly due to the flavonoids and esters of phenolic acids. 21 But it does not correlate with several other studies of Shingare and Chaugule, 1 Hedge and Kesaria, 22 and Mathew et al, 23 where it has been stated that propolis has minimal antibacterial effect against E. faecalis. The antimicrobial activity of neem was comparable to propolis and is considered to be due to its antiadherence activity by altering bacterial adhesion and their ability to colonize.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This effect of propolis is possibly due to the flavonoids and esters of phenolic acids. 21 But it does not correlate with several other studies of Shingare and Chaugule, 1 Hedge and Kesaria, 22 and Mathew et al, 23 where it has been stated that propolis has minimal antibacterial effect against E. faecalis. The antimicrobial activity of neem was comparable to propolis and is considered to be due to its antiadherence activity by altering bacterial adhesion and their ability to colonize.…”
Section: Discussionmentioning
confidence: 77%
“…1 Propolis (bee glue) is a resinous brown material collected by bees chiefly from plants like poplar and coniferous trees or clusia flowers. Flavonoids, the main constituent of propolis, are the active ingredient, with most of its properties like antioxidant, antimicrobial, anticancer, and anti-inflammatory.…”
Section: Ijoprdmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Other studies have also proved that tannins have antimicrobial activity against S. aureus 18 and oral microbiota. 19 The highly probable biochemical compounds in tannins that may be responsible for inhibiting and killing MRSA might have possessed lower MIC and MBC values.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative evaluation of antimicrobial activity of miswak, propolis, sodium hypochlorite and saline as root canal irrigants by microbial culturing and quantification in chronically exposed primary teeth was done showed that results of propolis was comparable to those of the negative control. 40 An in vivo randomized trial was conducted where root canals were irrigated using either 2% CHX, 4% calcium hydroxide or DMSO) extract of propolis with normal saline as the control irrigant. Which showed a significant decrease in mean aerobic colony forming units count in all the groups, however CHX was superior.…”
mentioning
confidence: 99%